کُتبِ اُصول حدیث اکیسویں صدی میں ؛ایک تعارفی جائزہ: An Introductory Review of the Books written on ‘Usūl e Ḥadīth in 2ist Century - Bibi, Sumaira; Ashiq, Shazia (Al-Amīr Research Journal for Islamic Studies, 2020)
Muslims are a unique nation in the world who have shown unparalleled activism in preserving their sayings and relics. Caution was in view from day one. The simple precautionary measures taken in the early days later took the form of theology. In the beginning, the principles and rules of this knowledge did not exist in a disciplined form, although the scholars of Muḥaddithin adhered to the basic principles of this knowledge from the very beginning. However, references to these principles were to be found in the books of the pious. In the 4th Hijri, the scholars of Muhaddithin compiled the previous scattered work on the art of the principle of Ḥadith. Now these comprehensive definitions and terms are before us in a systematic and disciplined form in the books of ‘Usūl e Ḥadīth. In this short essay, the definition and necessity and importance of Hadith and ‘Usūl e Ḥadīth have been highlighted and also an introductory review of books written on ‘Usūl e Ḥadīth th and their authors and authors has been presented. Which indicates this. How strict were the rules and regulations of the Muslim Ummah for examining the authenticity and text of the Holy Hadith and how did they separate the authentic, weak and subject matter of the hadiths and write their separate books? And how hard they have worked to promote art.